Effectiveness of Foeniculum vulgare leaf essential oil nanoemulsion as a natural insecticide against Aedes aegypti larvae and mosquitoes - ARUM TRIYAS WARDANI; TRIANA KUSUMANINGSIH; AHMAD AINUROFIQ (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wardani AT, Kusumaningsih T, Ainurofiq A. 2024. Effectiveness of Foeniculum vulgare leaf essential oil nanoemulsion as a natural insecticide against Aedes aegypti larvae and mosquitoes. Biodiversitas 25: 990-997. The control of dengue hemorrhagic fever (DHF) was by breaking the chain of transmission by controlling Aedes aegypti larvae and mosquitoes. One alternative to controlling mosquito larvae is to use natural materials because they are more environmentally friendly and do not cause harmful residual effects. This study used a Foeniculum vulgare Mill. (fennel) leaf as a natural insecticide to kill Ae. aegypti larvae and mosquitoes. Steam distillation was done to extract essential oils from the Foeniculum vulgare Mill. leaves. F. vulgare leaf essential oil was made as nanoemulsion with tween 80, PEG 400, essential oil, and aqua demineralized. GC-MS results showed that the main ingredients in F. vulgare. leaf essential oil were anethole, estragole, bicyclo[3.1.0]hex-2-ene, 4-methyl-1-(1-methyl ethyl)-,?-pinene, cyclohexene, 1-methyl-5-(1-methyl ethenyl)-, (R)-.The current study aimed to determine the effectiveness of an F. vulgare essential oil nanoemulsion as a larvicidal, adulticidal Ae.aegypti mosquito. The study results obtained LC50 values for each formula I, II, and III were 0.098, 0.317, 0.157 µL/mL, and LC90 values for each formula I, II, and III were 0.158, 0.416, 0.245 µL/mL. Fennel leaf essential oil nanoemulsion was tested on adult Ae. aegypti mosquitoes aged 3-5 days. The results of the study obtained LC50 values for each formula I, II, III were 7.768, 10.575, 5.069 g/m3, and LC90 values for each formula I, II, III were 15.191, 27.565, 8.892 g/m3. The difference in the effectiveness of each formula may be due to the large number of essential oils in the formula. F. vulgare leaf essential oil could be an environmentally friendly natural insecticide with less residual effect.